Interaction between honeybee mandibles and propolis - Saccardi, Leonie; Brümmer, Franz; Schiebl, Jonas; Schwarz, Oliver; Kovalev, Alexander; Gorb, Stanislav (Beilstein Journal of Nanotechnology, 2022)
In a biomimetic top-down process, challenging the problem of resin deposition on woodworking machine tools, an adequate biological model was sought, which hypothetically could have developed evolutionary anti-adhesive strategies. The honeybee (Apis mellifera) was identified as an analogue model since it collects and processes propolis, which largely consists of collected tree resin. Propolis is a sticky substance used by bees to seal their hive and protect the colony against pathogens. In spite of its stickiness, honeybees are able to handle and manipulate propolis with their mandibles. We wanted to know if beneficial anti-adhesive properties of bee mandibles reduce propolis adhesion. The anatomy of bee mandibles was studied in a (cryo-)scanning electron microscope. Adhesion experiments were performed with propolis on bee mandibles to find out if bee mandibles have anti-adhesive properties that enable bees to handle the sticky material. A scale-like pattern was found on the inside of the mandible. Fresh mandibles were covered with a seemingly fluid substance that was at least partially removed during the washing process. Propolis adhesion on bee mandibles was measured to be 1 J/m2 and was indeed significantly lower compared to five technical materials. Propolis adhesion was higher on mandibles that were washed compared to fresh, unwashed mandibles. Results indicate that the medial surface of the mandible is covered with a fluid substance that reduces propolis adhesion. First results suggested that the surface pattern does do not have a direct effect on propolis adhesion.
Keywords: adhesion; Apis mellifera; bee mandibles; honeybee; propolis

(untitled) - Saccardi, L.; Schiebl, J.; Weber, K.; Schwarz, O.; Gorb, S.; Kovalev, A. (Front. Mech. Eng., 2021)

(untitled) - Bankova, V. S.; de Castro, S. L.; Marcucci, M. C. (Apidologie, 2000)

(untitled) - Burdock, G. A. (Food Chem. Toxicol., 1998)

(untitled) - Simone-Finstrom, M.; Spivak, M. (Apidologie, 2010)

(untitled) - Bankova, V. (J. Ethnopharmacol., 2005)

Form and function in the honey bee - Goodman, L. (International Bee Research Association, 2003)

The anatomy of the honey bee - Snodgrass, R. E. (Washington: Government Printing Office, 1910)

(untitled) - Carreck, N. L.; Andree, M.; Brent, C. S.; Cox-Foster, D.; Dade, H. A.; Ellis, J. D.; Hatjina, F.; van Englesdorp, D. (J. Apic. Res., 2013)

(untitled) - Calderone, N. W. (Apidologie, 1998)

(untitled) - Nakamura, J.; Seeley, T. D. (Behav. Ecol. Sociobiol., 2006)

(untitled) - Alfonsus, E. C. (Glean. Bee Cult., 1933)

(untitled) - Kumazawa, S.; Nakamura, J.; Murase, M.; Miyagawa, M.; Ahn, M.-R.; Fukumoto, S. (Naturwissenschaften, 2008)

(untitled) - Park, Y. K.; Paredes-Guzman, J. F.; Aguiar, C. L.; Alencar, S. M.; Fujiwara, F. Y. (J. Agric. Food Chem., 2004)

(untitled) - Teixeira, É. W.; Negri, G.; Meira, R. M. S. A.; Message, D.; Salatino, A. (Evidence-Based Complementary Altern. Med., 2005)

(untitled) - Meyer, W.; Ulrich, W. (Bee World, 1956)

(untitled) - Voigt, D.; Gorb, S. (J. Exp. Biol., 2008)

(untitled) - Leonhardt, S. D.; Blüthgen, N. (Biotropica, 2009)

(untitled) - Gastauer, M.; Campos, L. A. O.; Wittmann, D. (Rev. Bras. Entomol., 2011)

(untitled) - Gastauer, M.; Campos, L. A. O.; Wittmann, D. (An. Acad. Bras. Cienc., 2013)

(untitled) - dos Santos, C. G.; Blochtein, B.; Megiolaro, F. L.; Imperatriz-Fonseca, V. L. (Neotrop. Entomol., 2010)

(untitled) - Bankova, V.; Bertelli, D.; Borba, R.; Conti, B. J.; da Silva Cunha, I. B.; Danert, C.; Eberlin, M. N.; I Falcão, S.; Isla, M. I.; Moreno, M. I. N.; Papotti, G.; Popova, M.; et al. (J. Apic. Res., 2019)

(untitled) - Gorb, E.; Kastner, V.; Peressadko, A.; Arzt, E.; Gaume, L.; Rowe, N.; Gorb, S. (J. Exp. Biol., 2004)

(untitled) - Gorb, S.; Scherge, M. (Proc. R. Soc. London, Ser. B, 2000)

(untitled) - Jiao, Y.; Gorb, S.; Scherge, M. (J. Exp. Biol., 2000)

(untitled) - Wheater, C. P.; Evans, M. E. G. (J. Insect Physiol., 1989)

Modern Research and Educational Topics in Microscopy - Gorb, S. N.; Voigt, D.; Gorb, E. V. (Visualisation of small fluid droplets on biological and artificial surfaces using the cryo-SEM approach, 2007)

(untitled) - Gorb, S. N.; Kesel, A.; Berger, J. (Arthropod Struct. Dev., 2000)

(untitled) - Koch, K.; Schulte, A. J.; Fischer, A.; Gorb, S. N.; Barthlott, W. (Bioinspiration Biomimetics, 2008)

(untitled) - Spurr, A. R. (J. Ultrastruct. Res., 1969)

(untitled) - Johnson, K. L.; Kendall, K.; Roberts, A. D. (Proc. R. Soc. London, Ser. A, 1971)

Theory of viscoelasticity - Christensen, R. (Academic Press, 1982)

(untitled) - Cheng, L.; Xia, X.; Scriven, L. E.; Gerberich, W. W. (Mech. Mater., 2005)

(untitled) - Kovalev, A.; Filippov, A.; Gorb, S. N. (J. Comp. Physiol., A, 2018)

(untitled) - Filippov, A.; Gorb, S. N. (Sci. Rep., 2013)

(untitled) - Vincent, J. F. V.; Wegst, U. G. K. (Arthropod Struct. Dev., 2004)

(untitled) - Locke, M. (J. Biophys. Biochem. Cytol., 1961)

Industrial solvents handbook, revised and expanded - Cheremisinoff, N. P. (Taylor & Francis, 2003)

(untitled) - Pal, R. (Bull. Entomol. Res., 1950)

(untitled) - Örösi-P´l, Z. (Bee World, 1957)

(untitled) - Dos Santos, C. G.; Megiolaro, F. L.; Serrão, J. E.; Blochtein, B. (Ann. Entomol. Soc. Am., 2009)

(untitled) - Fujita, T.; Kozuka-Hata, H.; Hori, Y.; Takeuchi, J.; Kubo, T.; Oyama, M. (PLoS One, 2018)

(untitled) - Zhang, C.-P.; Zheng, H.-Q.; Hu, F.-L. (J. Food Sci., 2011)

(untitled) - Ruguo, Z.; Hua, Z.; Hong, Z.; Ying, F.; Kun, L.; Wenwen, Z. (Procedia Eng., 2011)

(untitled) - Jander, R. (Physiol. Entomol., 1976)

(untitled) - Scherge, M.; Gorb, S. N. (Phys. Today, 2002)

(untitled) - Abou-Shaara, H.; Singl, A. R.; Al-Ghamdi, A. A. (Environ. Exp. Biol., 2013)

(untitled) - Kather, R.; Drijfhout, F. P.; Martin, S. J. (J. Chem. Ecol., 2011)

(untitled) - Helbig, R.; Nickerl, J.; Neinhuis, C.; Werner, C. (PLoS One, 2011)

(untitled) - Peisker, H.; Gorb, S. N. (J. Exp. Biol., 2010)

(untitled) - Lee, Y.; Matsushima, N.; Yada, S.; Nita, S.; Kodama, T.; Amberg, G.; Shiomi, J. (Sci. Rep., 2019)

(untitled) - Sun, W.; Tang, L.; Hong, W.; Zhan, Y.; Yang, B.; Liu, J. (RSC Adv., 2019)